Unsheltered : a novel - Kingsolver, Barbara (Harper, an imprint of HarperCollinsPublishers, 2018)
How could two hardworking people do everything right in life, a woman asks, and end up destitute? Willa Knox and her husband followed all the rules as responsible parents and professionals, and have nothing to show for it but debts and an inherited brick house that is falling apart. The magazine where Willa worked has folded; the college where her husband had tenure has closed. Their dubious shelter is also the only option for a disabled father-in-law and an exasperating, free-spirited daughter. When the family<U+2019>s one success story, an Ivy-educated son, is uprooted by tragedy he seems likely to join them, with dark complications of his own.